State-of-the-Art Large Language Model Performance on Reasoning Benchmarks - Assignee Research (Assignee Research, 2026)
This report synthesises findings from 4 peer-reviewed papers addressing the following research question: What are the state-of-the-art large language model results on reasoning benchmarks published recently v15. 14 claims were extracted from source literature; 1 was independently verified against retrieved documents. An automated multi-reviewer quality assessment produced a score of 4.2/10. This report is a machine-generated literature synthesis and does not constitute original research.
Machine-generated literature synthesis.